Lessons learnt from sexual and reproductive health and HIV linkages for multipurpose prevention technology service delivery. (October 2014) - Lusti‐Narasimhan, M; Collins, L; Hopkins, J
Abstract : Provision of comprehensive sexual and reproductive health (SRH) services that meet the complex and diverse needs of women, in particular, within resource‐constrained settings, is often exacerbated by separate and uncoordinated reproductive health (RH) and HIV policies and programmes. A Rapid Assessment Tool for Sexual and Reproductive Health and HIV Linkages was developed to assess bi‐directional linkages between SRH and HIV at policy, systems and service delivery levels, as well as to identify gaps and contribute to the development of country‐specific action plans. Findings from the implementation of this Assessment Tool are of particular relevance to the successful delivery and uptake of multipurpose prevention technologies (MPTs), which are products in the development pipeline addressing multiple SRH needs of women, including HIV. The findings highlight the need for better coordination between SRH and HIV programmes in countries; support and training for healthcare providers on SRH, HIV and human rights; supporting SRH and HIV integration at the service delivery level through relevant policies, strategic and operational plans; and strengthening logistics and supplies systems to provide a combination approach to prevention. These lessons learnt could help programme managers and service providers to better understand the strategies for positioning multipurpose prevention products in national policy and service contexts.